Clinical masks of infective endocarditis - Yu. V. Lobzin; A. S. Levina (Журнал инфектологии, 2015)
Currently diagnosis of infective endocarditis remains a challenge for physicians. The disease is diagnosed within 1 month after primary visit to a doctor only in 26% of cases, from 1 to 3 month – 40% of patients, and 34% – from 4 months to 1 year. In 10% of cases infective endocarditis was diagnosed at autopsy. Late diagnosis of infective endocarditis is associated with a polymorphism of a clinical picture, due to the development of systemic infection with embolic, thrombohemorrhagic, immune mechanism of damage to organs and tissues. The authors provide information about clinical «masks» of the disease, the most common of which are the mask of pneumonic, rheumatological, renal, cardiac, neurological and hematological diseases. The purpose of work – to acquaint specialists with the clinical picture of infectious endocarditis. The multidisciplinary nature of the problem of infective endocarditis requires orientation in her clinical picture primary care physicians and specialists in different fields.